Calibrating the Ediacaran-Cambrian transition in the SW Gondwana - Warren, L. V. [UNESP]; Tohver, E.; Inglez, L. [UNESP]; Okubo, J. [UNESP]; Riccomini, C.; Xiao, S. (Consejo Superior Investigaciones Cientificas-csic, 2019)
The paleontological, isotopic and geochronological data summarized below support the paleogeographic and temporal correlation between Itapucumi (Paraguay) and Corumba (Brazil) groups, suggesting a coeval sedimentary evolution of these units in the margins of the Amazon Craton and the Rio Apa Block.
Keywords: Itapucumi Group; SHRIMP ages; Detrital and volcanic zircon; Nama assemblage; Ediacaran Cambrian transition; SW Gondwana